Community Engagement Before Initiation of Typhoid Conjugate Vaccine Trial in Schools in Two Urban Townships in Blantyre, Malawi: Experience and Lessons. (7th March 2019) - Meiring, James E; Sambakunsi, Rodrick; Moyo, Elvis; Misiri, Theresa; Mwakiseghile, Felistas; Patel, Pratiksha; Patel, Priyanka; Ndaferankhande, John; Laurens, Matthew; Gooding, Kate; Gordon, Melita A
Abstract: Background: To determine the efficacy of a new typhoid conjugate vaccine in an endemic setting in sub-Saharan Africa, the Typhoid Vaccine Acceleration Consortium is conducting a phase-3 randomized controlled trial in Blantyre, Malawi. This article describes community and stakeholder engagement activities before and during the trial, challenges, and lessons learned. Methods: In October 2017, Malawi-Liverpool Wellcome Trust (MLW) organized a wide range of community engagement activities, including meetings with Ministry of Health and Education officials at the district and facility level, local community leadership, and parent teacher association groups. We engaged media outlets to include local and international television, radio, and print media. Community members were informed directly through a study jingle played via loudspeaker from a van and by community-based activities. To review engagement activity effectiveness: The MLW team met to discuss progress and challenges; and a focus group discussion (FGD), consisting of trial staff, sought feedback from the community on each engagement modality. Results: The school-based vaccine campaign increased community participation exceeding recruitment targets to date (on average, >200 children/day). Conclusions: The FGD concluded that the van and local activities improved awareness and turnout for the trial, but prior engagement with local government and community leadership is an essential mechanism to provide details of the study, answer questions, communicate the value of the study, and address safety concerns. Effective community engagement is essential in a large intervention trial. Multiple channels of communication are required to reach the community and deliver information needed for participation and provide opportunity for dialogue with the trial team.